2022
DOI: 10.2337/figshare.20610612.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urinary Zinc and Incident Type 2 Diabetes: Prospective Evidence from the Strong Heart Study

Abstract: <p>  </p> <p>Objective: Hyperglycemia can increase urinary zinc excretion. We evaluated  the association of higher urinary zinc with newly diagnosis of incident type 2 diabetes (T2DM incidence) in adult populations with a high burden of T2DM from Arizona, Oklahoma, North Dakota and South Dakota. We also assessed the cross-sectional association of urinary zinc levels with prevalent prediabetes.</p> <p><strong>Research Design and Methods:</strong> We included 1,339 adult… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Consistent with our findings, a 20-year prospective cohort study in middle-aged and older Finnish men revealed that the risk of T2D increased with increasing serum Zn concentration, possibly due to the effect of Zn on BMI and insulin sensitivity [44]. Some studies have shown that urinary Zn levels are also positively associated with diabetes [45,46]. Moreover, a positive correlation between Zn and T2D can also be found in plasma [40].…”
Section: Molybdenumsupporting
confidence: 91%
“…Consistent with our findings, a 20-year prospective cohort study in middle-aged and older Finnish men revealed that the risk of T2D increased with increasing serum Zn concentration, possibly due to the effect of Zn on BMI and insulin sensitivity [44]. Some studies have shown that urinary Zn levels are also positively associated with diabetes [45,46]. Moreover, a positive correlation between Zn and T2D can also be found in plasma [40].…”
Section: Molybdenumsupporting
confidence: 91%